Perencanaan Sistem Penyediaan Air Minum Di Desa Lolo Wano, Kecamatan Tanarighu Kabupaten Sumba Barat, Nusa Tenggara Timur - I Ketut Nuraga; DEWA AYU PUTU ADHIYA GARINI PUTRI (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
Lolo Wano Village, located in the Tanarighu District in West Sumba is classified as a a critical water area, especially for domestic water supply. To address the critical of domestic water situation, the design of the domestic Water Provision System can utilize the water from Wee Tame Water Spring in the forest area at Lolo Wano Village. The method of the water provision for the society at Lolo Wano Village involves the pumping plant for water spring resources (El. +97,52 m) to the Reservoir 1 (El. +231,65 m) and then distributing it to the service area through a gravity flow system using transmissions pipes. The pump pipes are made of galvanized steel (GIV) with a diameter of 2.5 inches and a length of 681m. The transmission pipes are made of High-Density Polyethylene (HDPE) with a diameter of 2,5 inches and a length of 1.428,52 m to Lokory Village and pipes with a diameter of 1,5 inches and length to 976 m long to Lolo Wano Village. The pumping plant requires a power of 10,188 kW and generates a starting current of 68,391 Amperes.